HPV-related information sharing and factors associated with US men's disclosure of an HPV test result to their female sexual partners - Marhefka, Stephanie L (2012)
OBJECTIVES: Prevalence of human papillomavirus (HPV) is high in both men and women, yet men have seldom been involved in HPV education/prevention programmes, and their disclosure of known HPV infection has rarely been studied. This analysis sought to determine factors associated with men's HPV test result disclosure and HPV-related information sharing with partners. METHODS: From 2007 to 2010, men enrolled in a psychosocial study of responses to HP testing who reported having a female main sexual partner (N=251) completed surveys including questions about HPV test results, disclosure of HPV test results to partner(s), relationship characteristics and stigma (for those who reported HPV-positive results) approximately 3 weeks after receiving an HPV test result. Logistic regression was conducted to determine factors associated with disclosure of HPV test results in cross-sectional analysis. RESULTS: Most men disclosed their test results to a main partner (82%). Self-reported HPV-negative test result, a high school education and a higher commitment to a sexual partner were significantly associated with increased disclosure in multivariable analysis. Men who disclosed (vs those who did not) were significantly more likely to provide their partners with HPV-related information. Among men who disclosed to their main partner, nearly half reported that partner asked them questions about HPV. CONCLUSIONS: Results from this study highlight the critical role that men who are symptomatic for, who are tested for or who are vaccinated against HPV can play in educating their sexual partners, independent of whether they actually disclose their test results.